Antilymphocytic Serum in Experimental Allergic Encephalomyelitis. Issue 5673 (27th September 1969) - Field, E. J.
Abstract : Antilymphocytic and antithymic sera (raised in rabbits) are highly potent in preventing or alleviating experimental allergic encephalomyelitis in guinea-pigs. Good results are obtained when treatment is begun as late as 10 days after challenge. No protracted disease was seen from the use of antilymphocytic serum. Attempts to use this serum therapeutically once the disease was clinically established gave equivocal results. Antilymphocytic serum appears to have a non-specific stressor effect as well as its specific action, and possibly this adrenocorticotrophic-hormone (antiphlogistic) effect may ameliorate a developing encephalitis. The presence of an antimacrophagic factor in antilymphocytic serum may be important in increasing local reaction to injection of the serum and perhaps also in diminishing the appearance of haematogenous elements in the nervous lesions.